Targeting Immune-Mediated Dormancy: A Promising Treatment of Cancer - Wang, Hao-fan; Wang, Sha-sha; Huang, Mei-chang; Liang, Xin-hua; Tang, Ya-Jie; Tang, Ya-ling (Frontiers in Oncology, 2019)
Immune-mediated dormancy is that the immune system keeps proliferating tumor cells unchanged mostly via cytotoxic activity of immune cells. Cancer dormancy, especially immune-mediated dormancy, may be the explanation for tumor refractory and be responsible for resistance to conventional chemo- and radiotherapies. Here, we will describe different scenarios of how the immune cells and cytokines involved in cancer progression are connected with the initiation of dormancy and cancer treatment. Two distinct treatments such as maintaining metastatic tumor cells dormant and awakening them are also discussed. A better understanding of immune-mediated dormancy would help to design novel and effective immunotherapies and likely to increase the efficiency of tumor treatment inhibiting metastasis.